Evaluation of the developmental outcome in children with congenital hypothyroidism - Razieh Ehsani; Morteza Alijanpour; Mohammadreza Salehiomran; Farzan Kheirkhah; Leila Moslemi; Faeze Aghajanpour (Babol University of Medical Sciences, 2021)
Background: Congenital hypothyroidism (CH) is one of the most common endocrine diseases and one of the major causes of mental retardation in children. So we aimed to evaluate the developmental outcome of children with CH. Methods: This case-control study was performed on two 3-6-year-old groups of 100 patients. The case group was children with CH, referred to Endocrine Clinic of Amirkola Childrenchr('39')s Hospital (2011-2017) and the control group was healthy children and normal from other states. The Denver developmental screening test-II (DDST_II) was used to assess the developmental factors and disorders in four areas of gross motor, fine motor, personal-social and language. Data were analyzed by SPSS 21 using descriptive statistics, t-test and chi-square, and a p<0.05 was considered significant. Results: The mean age of 200 children in the case and control groups was 54.62±15.72 and 59.68±15.64 months, respectively. In the case group, 45% and 55% of them had transient and permanent CH, respectively. All four criteria of DDST_II in the control group as well as gross motor in the case group were normal, but fine motor, personal-social and language were reported normal in 94, 95 and 93% of the case group, respectively. All subjects with abnormal DDST_II, had a negative neonatal screening tests. Conclusion: The results obtained from DDST_II indicated that 6% of children with CH had an abnormal development, all who had an onset of medical treatment over 30 days, which makes it important to screen the neonatal thyroid disease and diagnose this disease timely.